Influence of Oxidative Stress-Related Genes on Susceptibility to Fibromyalgia. Issue 1 (January 2021) - Rus, Alma; Robles-Fernandez, Inmaculada; Martinez-Gonzalez, Luis Javier; Carmona, Ramon; Alvarez-Cubero, Maria Jesus
Abstract : Background: Fibromyalgia (FM) is a complex syndrome to diagnose and treat because of its unknown etiology. However, previous studies reported that patients with FM experience oxidative stress. Objectives: In this study, we investigated single-nucleotide polymorphisms (SNPs) in genes encoding enzymes involved in oxidative stress (superoxide dismutase 1 [SOD1], catalase, and NADPH oxidase [CYBA]) in patients with FM and in healthy subjects, as well as the possible relation with demographic and clinical manifestations of FM. Methods: A total of 141 patients with FM and 73 healthy subjects participated in this case–control study. For DNA extraction, buccal swabs were collected from patients with FM, and a peripheral blood sample was extracted from controls. We analyzed SNPs in genes related to oxidative stress (rs10432782 in SOD1, rs1001179 in catalase, and rs4673 in CYBA) using TaqMan probes. In patients with FM, severity of FM, fatigue, and pain were assessed by Fibromyalgia Impact Questionnaire, Multidimensional Fatigue Inventory, and Visual Analogue Scale (VAS), respectively. Physical (PCS-12) and mental (MCS-12) health statuses were evaluated by the 12-Item Short-Form Health Survey. Results: The selected SNPs did not show significant differences between patients with FM and controls. The rs10432782 (SOD1) was associated with Fibromyalgia Impact Questionnaire scores in patients with FM, whereas the rs4673 (CYBA) was associated with the Multidimensional Fatigue Inventory score, MCS-12 score, and duration of the disease. Discussion: We have identified significant correlations between SOD1 and CYBA variants with clinical manifestations of FM. These results provide new insights into the pathogenesis of FM that could be useful for guiding future studies along the way to find the cause(s) of this syndrome. Abstract : Supplemental digital content is available in the text.